Sulfated Ceria Catalyzed Synthesis of Imidazopyridines and Their Implementation as DNA Minor Groove Binders. Issue 5 (10th April 2019) - Mohan, Surender; Rangappa, Shobith; Anilkumar, Nirvanappa C.; Fuchs, Julian E.; Bender, Andreas; Basappa,; Rangappa, Kanchugarakoppal S.; Bhatnagar, Rakesh
Abstract: The small molecules that bind to DNA minor groove are considered as potential therapeutic agents to fight against many human diseases. They induce cell death by interfering with transcription, replication and progression of cell cycle. Herein, we report the synthesis of imidazopyridine‐3‐amines using sulfated ceria catalyst by employing Groebkee–Blackburne–Bienayme reaction. We evaluated the possible antiproliferative and antimycobacterial activity against A549 cells and Mycobacterium tuberculosis, respectively. Among the tested compounds, N ‐ tert ‐butyl‐2‐(2‐butyl‐4‐chloro‐1 H ‐imidazol‐5‐yl)‐5, 7‐dimethylimidazo[1, 2‐ a ]pyridin‐3‐amine (4g ) was identified as cytotoxic heterocycle and antimycobacterial agent. Molecular docking studies of the imidazopyridine derivatives revealed the consistent positioning in the minor groove with a tight shape fit between receptor and ligands. Therefore, we speculate that new imidazopyridines induce their pharmacological effect by targeting the minor groove of DNA. Abstract :